Fenomena Crossdressing: Antara Kebebasan Berekspresi Dan Etika Sosial Dalam Islam - Salsabila, Putri; Tri Dewantara, Rinanza; Wafa, Anida; Hanifah, Dela; Haryanti, Claura; Muhammad Noor, Aditia (At-Tuhfah : Jurnal Studi Keislaman, 2023)
Cross dressing is the act of someone wearing and dressing according to a different gender compared to their own gender. That is, this crossdressing is a deviant behavior towards a way of looking and behaving that is not in accordance with one's gender. Most of those who behave crossdressing is a gender minority. In Indonesia, the phenomenon of crossdressing is widely found, even as time goes by, variations of this crossdressing spread to the clothes worn by Muslim women. With the style of a long, closed robe, wearing a veil, and sometimes wearing a hijab, it is possible that everyone who wears the clothes is not of their original gender. Another term that can define the previous statement is crosshijaber. In this study using the method of literature study or library research using a qualitative descriptive approach in explaining the overall causes of the phenomenon of crossdressing in society. This research method is carried out by searching and reading several reference sources that will be used as references and written forms such as articles, journals, and others. The results of the research conducted can be concluded that the beginning of the phenomenon of crossdressing came from the Egyptian kingdom and spread to various regions. The phenomenon of crossdressing itself is one of the effects of the times. In Indonesia itself, the perpetrators of crossdressing have been alluded to from an Islamic perspective, which in essence is considered to be against predetermined fate and is not at all justified. This crossdressing is not only causing criminal acts or sexual acts which only lead to disobedience